2022
DOI: 10.29407/jpdn.v8i1.18069
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Impact of Imitating Online Game Sakura School Simulator

Abstract: :This research was conducted against the background of the impact on students playing the online game sakura school simulator on changes in social behavior imitating elementary school students. The purpose of this study was to determine the impact of students playing the online game sakura school simulator on the social behavior of imitating students at Madarasah Ibtidaiyah. This study uses qualitative methods with case study instruments, collecting data from online game players through direct observation, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Betawi art, namely Ondel.-Ondel, and traditional games, namely Sondah and Marbles (Ganda & Hidayat, 2021;Nurazizah et al, 2023). By connecting the results of observations and the theory of Observational Learning and Imitation, broadcasting audiovisual media such as animated series will influence behavior and shape character based on what is observed and imitated from examples or role models (M. Jannah & Wardana, 2022;Rhoads, 2022). So that the animated series media made in Indonesia is Adit & Sopo animation Jarwo can be used as an effective character education medium in cultivating the character of mutual cooperation and independence in elementary school students.…”
Section: Discussionmentioning
confidence: 99%
“…Betawi art, namely Ondel.-Ondel, and traditional games, namely Sondah and Marbles (Ganda & Hidayat, 2021;Nurazizah et al, 2023). By connecting the results of observations and the theory of Observational Learning and Imitation, broadcasting audiovisual media such as animated series will influence behavior and shape character based on what is observed and imitated from examples or role models (M. Jannah & Wardana, 2022;Rhoads, 2022). So that the animated series media made in Indonesia is Adit & Sopo animation Jarwo can be used as an effective character education medium in cultivating the character of mutual cooperation and independence in elementary school students.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted [6] showed that participants who played the simulation game, namely Sakura School Simulator, found that the behavior presented by the characters in the game was able to be imitated and influenced the behavior of the players. The experience in the school simulation game gained from playing the game influences the behavior of the players.…”
Section: Introductionmentioning
confidence: 99%